Efficacy of Cognitive Behavioral Therapy for Generalized Anxiety Disorder in Older Adults: Systematic Review, Meta-Analysis, and Meta-Regression - Berrios-Espinoza, R (Elsevier B.V., 2016)
Objective Generalized anxiety disorder (GAD) is a common disorder in older adults producing functional impairment, and psychotherapy is the preferred treatment option. Meta-analytic methods sought to determine the efficacy of outpatient cognitive behavioral therapy (CBT) with respect to the hallmark feature of GAD—uncontrolled and excessive worry. In order to optimize clinical applicability, variables associated with GAD treatment outcomes were also examined. Methods Systematic search of relevant databases and iterative searches of references from articles retrieved. All studies were required to have been a randomized control trial (RCT), to have used the Penn State Worry Questionnaire (PSWQ) or its abbreviated version (PSWQ-A) as an outcome measure, and to have conducted CBT with outpatient older adults. Fourteen RCTs (N = 985) were suitable and random-effects meta-analyses and univariate meta-regressions were conducted. Results At the end of treatment, and at 6-month follow-up, significant treatment effects favoring CBT were found in comparison to a waitlist or treatment-as-usual. When CBT was compared with active controls, a small nonsignificant treatment advantage was found for CBT at the end of treatment, with equivalence of outcomes at follow-up. Treatment effect size of CBT for GAD was significantly associated with attrition rates and depression outcomes. Conclusions CBT is more helpful than having no treatment for GAD in later life. Nevertheless, whether CBT shows long-term durability, or is superior to other commonly available treatments (such as supportive psychotherapy), remains to be tested. The relationship between treatment effects for GAD and depression following CBT warrants further research. © 2016 American Association for Geriatric Psychiatry